DIGITAL TEXTBOOK OF ENGINEERING MECHANICS WITH A SCIENCE PROCESS AND ETHNOSCIENCE APPROACH FOR VOCATIONAL COLLEGE STUDENTS - Polonia, Betti Ses Eka; Ravi, Ahmad (Jurnal Ilmu Pendidikan Indonesia, 2024)
Students at the vocational higher education level prepare to become graduates and are ready to be used by industry. The objectives of vocational higher education are to develop other skills and valuable training for students facing the industry world in the future. This skill is called scientific skill. Students need to be involved in various appropriate activities in the learning process to develop students' scientific skills. Students need scientific skills to design their work steps, process skills, and report practicum results in reports and presentations. Ethnoscience is related to the culture of a society. It contains local or original science, where knowledge has become part of a society's culture and is passed down from generation to generation. Students learn by integrating scientific science with original science so that students make more sense in learning. Living knowledge in society can be transformed into scientific knowledge and used as a good learning resource for students. Ethnoscience-based textbooks can be a suitable learning resource to support culture-based learning activities from the natural environment realized in textbooks and audio-visuals. The validation of ethnoscience-based textbooks obtained 3.28 points over 4, which includes the feasible-to-use category